Novel N, S polycyclic aromatic hydrocarbon molecule and preparation thereof, and porous organic polymer gel constructed by using novel N, S polycyclic aromatic hydrocarbon molecule
By synthesizing N,S fused-ring aromatic hydrocarbon molecules to prepare porous organic polymer gels, the problem of difficult processing of porous organic polymer materials was solved, efficient photocatalytic water oxidation to produce H2O2 was achieved, and the practical application of photocatalysts was promoted.
Patent Information
- Application Number
- CN202410385698.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-01
- Publication Date
- 2025-10-14
AI Technical Summary
Existing porous organic polymer materials are difficult to process, which limits their practical applications, and existing photocatalysts have failed to achieve large-scale industrial production of H2O2.
N,S fused-ring aromatic hydrocarbon molecules are synthesized and porous organic polymer gels are prepared through hydrothermal reaction. Organic monomers containing aldehydes and catalysts are combined to react under specific conditions to form processable porous organic polymer gels for use in photocatalytic materials.
The prepared porous organic polymer gel exhibited excellent processability and efficient H2O2 generation rate under photocatalysis, which was 4435 μmol g-1h-1 under pure water conditions and 8240 μmol g-1h-1 under benzyl alcohol conditions.
Smart Images

Figure CN120774935A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of functional porous materials, and particularly relates to a novel N, S fused ring aromatic molecule and preparation thereof, and preparation of a porous organic porous polymer gel constructed by using the fused ring aromatic molecule and application of the porous organic porous polymer gel in photocatalytic water oxidation to generate hydrogen peroxide. BACKGROUND
[0002] Porous organic polymers are a new type of porous materials that have appeared in recent decades. Due to the high porosity and low skeleton density of porous organic polymers, the structure can be designed, the skeleton can be functionalized, and the stability is high. Therefore, more and more people pay attention to this kind of material. According to the structural characteristics and preparation methods, porous organic materials can be divided into intrinsic microporous polymers (PIMs), hypercrosslinked polymers (HCPs), conjugated microporous polymers (CMPs), covalent organic frameworks (COFs), covalent triazine frameworks (CTFs), porous aromatic frameworks (PAFs) and the like. Due to the excellent modifiability of this kind of material, we can accurately control the pore size, pore environment and specific surface area of the porous organic polymer on the atomic level by using the easily modified characteristics of the organic building unit to obtain an organic porous framework structure with specific structure and specific function. These characteristics make porous organic polymers have more extensive application value, so they are highly concerned in the field of material science. With the enrichment of synthesis reactions and the continuous expansion of application technology, porous organic frameworks show a very potential application prospect in the field of interfacial chemistry such as gas storage and separation, catalysis, sensing, energy storage and photoelectric conversion. Since porous organic polymers are essentially still high molecular compounds with high crosslinking degree, the preparation process is a rapid crosslinking process, resulting in the porous organic polymers in the form of insoluble and infusible powder after reaction. Due to the characteristics of insolubility and infusibility, the processing of porous organic polymers is hindered, which greatly limits the development of organic porous polymers in practical applications. Therefore, it is of great scientific significance to develop a preparation method of processable porous organic polymer gel.
[0003] Hydrogen peroxide as an oxidant plays a vital role in chemical industry, healthcare and water treatment. The annual demand of H2O2 is about 4 million tons worldwide and is still increasing in the past decades. It is estimated that the market demand of H2O2 will increase to 5.7 million tons by 2027. H2O2 is usually synthesized in industry by anthraquinone process: anthrahydroquinone (AHQ) obtained by catalytic hydrogenation of 2-ethylanthraquinone (AQ) is continuously produced by oxidation in air to form anthraquinone again. This anthraquinone process involves multi-step hydrogenation and oxidation reactions, is highly energy-intensive, has side reactions that consume anthraquinone, and requires complex processes for solution and catalyst regeneration, product separation and purification, resulting in high energy consumption, environmental pollution and lack of sustainability. Another feasible route is to use noble metal-based catalysts such as Pd, Au and Pt to directly synthesize H2O2 from a mixture of H2 and O2. Due to the potential risk of explosion, this process has not been scaled up to industrial production.
[0004] The way of using semiconductor photocatalysts to produce H2O2 from water and oxygen by artificial photosynthesis has attracted much attention due to its potential for low energy consumption and reduction of pollution and improvement of safety. However, so far, no photocatalyst can realize large-scale industrial production of H2O2 and be put into practical application. Porous organic polymers have become potential semiconductor photocatalysts for producing H2O2 due to their adjustable chemical structure, wide light absorption range and metal-free. The integrity of porous organic polymer gel enables the free transport of carriers generated by gel illumination on the water-photocatalyst interface, so that the porous organic polymer gel has significant photocatalytic activity for generating H2O2 and has a significant generation rate.
[0005] The present application has important significance for the practical application of porous organic polymers in photocatalysis by combining processable gel and photoactive phase to improve catalytic performance. SUMMARY
[0006] The present application aims to synthesize a new N, S fused ring aromatic molecule with excellent photoactivity, and synthesize a porous organic polymer gel using the N, S fused ring aromatic molecule, and apply the obtained porous polymer gel to photocatalytic materials, and find that its comprehensive performance such as processability and photocatalytic performance is improved compared with existing porous organic polymers.
[0007] Technical scheme of the present application:
[0008] The first technical problem to be solved by the present application is to provide an N, S fused ring aromatic molecule (DTTzDo), the structural formula of which is shown as formula I:
[0009]
[0010] A second technical problem to be solved by the present application is to provide a preparation method of the N, S fused ring aromatic molecule, which is prepared by using a hydrothermal reaction to prepare the N, S fused ring aromatic molecule from an organic monomer and a reaction solvent; wherein the organic monomer is 2,2'-((1,2,4,5-tetrazine-3,6-diyl)bis(sulfonamido))diacetic acid, and the reaction solvent is at least one of N,N-dimethylacetamide (DMA), methanol (MeOH) or N,N-dimethylformamide (DMF).
[0011] Further, the hydrothermal reaction is carried out at 60-120℃ for 3-5 days.
[0012] Further, the preparation method of the N, S fused ring aromatic molecule is specifically as follows: the 2,2'-((1,2,4,5-tetrazine-3,6-diyl)bis(sulfonamido))diacetic acid organic monomer and the reaction solvent are ultrasonically treated to fully dissolve the organic monomer, then added into a reaction kettle, and placed in an oven at a temperature of 60-120℃ (preferably 60℃) for reaction for 3-5 days (preferably 3 days), and then cooled to room temperature to obtain the N, S fused ring aromatic molecule (DTTzDo).
[0013] A third technical problem to be solved by the present application is to point out the use of the N, S fused ring aromatic molecule in preparing a porous organic polymer gel, an organic optoelectronic material or a catalytic material.
[0014] A fourth technical problem to be solved by the present application is to provide a porous organic polymer gel, which is prepared by reacting an aldehyde group-containing organic monomer and the N, S fused ring molecule (DTTzDo) synthesized above; wherein the aldehyde group-containing organic monomer contains at least four aldehyde groups.
[0015] Further, the aldehyde group-containing organic monomer is at least one selected from 4,4',4”,4”'-(ethene-1,1,2,2-tetrayl)tetraphenylaldehyde (ETTAB), 1,3,6,8-tetra(4-formylphenyl)pyrene (Py-4CHO), hexakis(4-formylphenyl)benzene (FHPB), 1,2,4,5-tetra(4-formylphenyl)benzene (TFBP).
[0016] Further, the molar ratio of the aldehyde group-containing organic monomer to the N, S fused ring molecule (DTTzDo) is 0.04-0.10:0.08-0.20.
[0017] A fifth technical problem to be solved by the present application is to provide a preparation method of the porous organic polymer gel, which comprises: reacting an aldehyde group-containing organic monomer and the N, S fused ring molecule (DTTzDo) at 110-140°C for 2-7 days in the presence of a solvent 1 and a catalyst to obtain the porous organic polymer wet gel; wherein the solvent 1 is N, N-dimethylacetamide (DMA) or N, N-dimethylformamide (DMF); and the catalyst is selected from the group consisting of pure acetic acid, triethylamine, phosphoric acid and triisopropylamine.
[0018] Further, in the preparation method of the porous organic polymer gel, the molar volume ratio of the aldehyde group-containing organic monomer to the solvent 1 is 0.05-0.10 mmol: 1 mL.
[0019] Further, in the preparation method of the porous organic polymer gel, the volume ratio of the catalyst to the solvent 1 is 0.05-0.20: 0.5-1.
[0020] Further, the preparation method of the porous organic polymer gel specifically comprises: ultrasonic treatment of the aldehyde group-containing organic monomer, the N, S fused ring molecule and the solvent 1 to fully dissolve the aldehyde group-containing organic monomer, then adding the catalyst and placing the reaction device in liquid nitrogen for freezing, and then performing at least three cycles of freezing-vacuumizing-thawing to exhaust the air in the reaction device, then sealing the reaction device with a 600-1200°C flame gun, and then drying at 110-140°C (preferably 120°C) for 2-7 days (preferably 3 days) to obtain the porous organic polymer gel wet gel.
[0021] Further, the obtained porous organic polymer gel wet gel can be processed into a dry gel, for example, by solvent soaking and supercritical CO2 drying to obtain a dry gel. For example, the wet gel is placed in a solvent containing N, N-dimethylformamide for 3 days, then taken out and placed in a solvent containing ethanol for 3 days, and then subjected to supercritical CO2 drying to obtain a dry gel.
[0022] A sixth technical problem to be solved by the present application is to provide the use of the porous organic polymer gel in photocatalysis, gas separation, ion conduction, ion separation or molecular separation.
[0023] A seventh technical problem to be solved by the present application is to provide a photocatalytic material, which is an aerogel material prepared by reacting an aldehyde group-containing organic monomer and the N, S fused ring molecule (DTTzDo) synthesized as described above.
[0024] Further, the photocatalytic material has a H2O2 production rate of 4435 μmol g -1 h -1 .
[0025] Further, the photocatalytic material has a rate of 8240 μmol g -1 h -1 .
[0026] The eighth technical problem to be solved by the present application is to provide a preparation method of the above-mentioned photocatalytic material, which comprises the following steps: first, reacting an aldehyde-containing organic monomer and the N,S fused ring molecule (DTTzDo) prepared above in a solvent 1 and a catalyst at 110-140 DEG C for 2-7 days to prepare a porous organic polymer wet gel; and then processing the wet gel into a dry gel to obtain the photocatalytic material; wherein the solvent 1 is N,N-dimethylacetamide (DMA) or N,N-dimethylformamide (DMF); and the catalyst is selected from pure acetic acid, triethylamine, phosphoric acid or triisopropylamine.
[0027] The present application has the following advantages:
[0028] The present application provides a novel N,S fused ring aromatic molecule and a synthesis method thereof; and the molecule is used as a building unit to synthesize a porous organic polymer gel, and the synthesized gel has excellent processability and photoelectric activity, which makes the gel exhibit excellent photocatalytic water oxidation rate when used as a photocatalytic material; the photocatalytic material has a rate of 4435 μmol g -1 h -1 ; and the photocatalytic material has a rate of 8240 μmol g -1 h -1 . BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 It is a reaction schematic diagram of the novel N,S fused ring aromatic molecule (DTTzDo) obtained in Example 1 of the present application.
[0030] Figure 2 It is a reaction schematic diagram of the porous organic polymer gel obtained in Example 2 of the present application.
[0031] Figure 3 It is a real object diagram of the wet gel corresponding to different concentrations of the same monomer obtained in Examples 2-4 of the present application.
[0032] Figure 4 It is a nuclear magnetic resonance spectrum of the novel N,S fused ring aromatic molecule (DTTzDo) obtained in Example 1 of the present application.
[0033] Figure 5 It is a mass spectrum of the novel N,S fused ring aromatic molecule (DTTzDo) obtained in Example 1 of the present application.
[0034] Figure 6 Infrared spectra of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0035] Figure 7 Gas adsorption spectra of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0036] Figure 8 (a) UV-Vis diffuse reflectance spectra and (b) corresponding Tauc plots of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0037] Figure 9 Photocurrent plots of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0038] Figure 10 Mott-Schottky plots of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0039] Figure 11 Band diagrams of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application examples 2-4.
[0040] Figure 12 H2O2 generation rate plots of ETTAB-DTTzDo-AG samples of different monomer concentration for the materials of the present application example 2 under different sacrificial reagents. DETAILED DESCRIPTION
[0041] The present application provides a new type of N, S fused ring aromatic molecule and uses it as a building unit to form a porous organic polymer gel and a corresponding gel photocatalytic material, which can be prepared by the following steps:
[0042] Step one: the organic monomer 2,2'-((1,2,4,5-tetrazine-3,6-diyl)bis(sulfonamido))diacetic acid can be reacted by hydrothermal reaction to form an N, S fused ring aromatic molecule (DTTzDo) under the condition of using DMA:MeOH=1:1 (V:V) or DMF as the reaction solvent;
[0043] Step two: the DTTzDo molecule and the organic monomer containing an aldehyde group can be dissolved in DMA as the solvent and acetic acid as the catalyst to form a porous organic polymer wet gel;
[0044] Step three: the synthesized wet gel is dried to obtain a dry gel as a photocatalytic material.
[0045] The embodiments of the present application will be described in detail below with examples, but those skilled in the art will understand that the following examples are only for illustration of the present application and should not be regarded as limiting the scope of the present application. The specific conditions not noted in the examples are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used are not noted by the manufacturer, which are all conventional products that can be obtained by commercial purchase.
[0046] Example 1 Preparation of a novel N, S fused ring aromatic molecule (DTTzDo)
[0047] In a 25 mL hydrothermal reactor, 2,2'-((1,2,4,5-tetrazine-3,6-diyl)bis(sulfonamido))dibenzoic acid (0.04 mmol) and DMA:MeOH = 1:1 (volume ratio V:V, 10 mL) or DMF (10 mL) were added and ultrasonicated for 10 min to make the monomer fully dissolved in the solvent. After being placed in an oven at 60°C for 3 days, it was cooled to room temperature and then taken out to obtain the product DTTzDo.
[0048] Example 2 Preparation method of porous organic polymer gel
[0049] 1) In a 10 mL ampoule, DTTzDo (0.10 mmol) and 4,4',4”,4”'-(ethene-1,1,2,2-tetrayl) tetrakisbenzaldehyde (ETTAB) (0.05 mmol) were added in DMA (1 mL) and ultrasonicated for 10 min to make the monomer fully dissolved in the DMA solution (the concentration of the organic monomer is recorded as 50 mM). 0.10 mL of pure acetic acid was added and the ampoule was immediately connected to a double-tube and placed in liquid nitrogen for freezing. After three cycles of freezing-vacuumizing-thawing, the air in the ampoule was exhausted, and then it was sealed with a high-temperature flame gun and placed in an oven at 120°C for 3 days. After cooling to room temperature, the wet gel (ETTAB-DTTzDo-G) was taken out.
[0050] 2) The wet gel obtained in step 1) was taken out from the ampoule and placed in N,N-dimethylformamide for 3 days, and the solution was changed every day. After 3 days, it was taken out and placed in a solvent containing ethanol, which was also changed every day. After 3 days, it was taken out and then supercritical CO2 drying was carried out to obtain the dry gel (ETTAB-DTTzDo-AG).
[0051] Examples 3-4
[0052] The preparation process is the same as Example 2, the only difference is that the concentration of organic monomer is changed in step 1) (i.e. the molar volume ratio of tetraaldehyde tetraphenyl ethane (ETTAB) to DMA in Example 2 is changed) respectively: 60mM (Example 3), 70mM (Example 4); the results show that gels can be obtained (as shown in Figure 3
[0053] Structural characterization of test example 1
[0054] 1) NMR and mass spectrum of DTTzDo sample
[0055] First, the DTTzDo sample obtained in Example 1 is dissolved in deuterated DMSO for hydrogen spectrum test (as shown in Figure 4 , and dissolved in methanol for mass spectrum test (as shown in Figure 5 , from the NMR and mass spectrum, it can be known that the obtained DTTzDo sample is pure.
[0056] Structural characterization of test examples 2-4
[0057] 1) Infrared spectrum of ETTAB-DTTzDo-AG sample with different monomer concentrations
[0058] First, the ETTAB-DTTzDo-AG sample with different monomer concentrations and potassium bromide are placed in a vacuum oven and dried overnight at 80°C, and a sample with a diameter of about 1.2 cm is prepared by using an infrared pressing die, and the sample is tested by infrared. As shown in Figure 6 : compared with ETTAB and DTTzDo monomers, ETTAB-DTTzDo-AG shows a new C=C vibration peak at 1610 cm -1 . At the same time, the peak at 1700 cm -1 corresponding to the aldehyde group C=O vibration in ETTAB monomer and the C-H vibration absorption peaks at 2940 and 2990 cm -1 in DTTzDo monomer disappear in ETTAB-DTTzDo-AG sample, so it can be known from the infrared spectrum that the reaction occurs.
[0059] 2) N2 adsorption spectrum of ETTAB-DTTzDo-AG sample with different monomer concentrations
[0060] A certain amount of sample is weighed in a sample tube, and after vacuum drying treatment, the sample is tested for N2 adsorption by setting the program, as shown in Figure 7 As shown in the figure, the sample exhibits a typical II-type adsorption curve. The adsorption amount is large in the low pressure range of P / P0<0.001, and the adsorption amount is large in the low pressure range of 0.001. <P / P0<0.8的中压范围内吸附量略有增加,与ETTAB-DTTzDo-AG的微孔和介孔率相对应。值得注意的是,在0.8<P / P0<1的高压范围内,由于氮气在气凝胶表面的毛细凝结,ETTAB-DTTzDo-AG的吸附量急剧增加,从而揭示了ETTAB-DTTzDo-AG的大孔隙性。
[0061] Photoelectric performance characterization of experimental examples 2 to 4
[0062] 1) Optical properties test of ETTAB-DTTzDo-AG samples with different monomer concentrations
[0063] After mixing and grinding ETTAB-DTTzDo-AG samples with different monomer concentrations and barium sulfate, the samples were pressed into sheets with a glass rod and placed in an absorption spectrometer. All tests were completed on a Shimadzu UV-3600. The absorption spectrum shows that the polymer has good absorption in the range of 300-800nm. At the same time, according to calculations, the optical band gaps of ETTAB-DTTzDo-AG samples with different monomer concentrations are 2.26eV, 2.20eV and 2.22eV, respectively, indicating that the ETTAB-DTTzDo-AG sample has a certain absorption capacity in a wide spectrum (such as Figure 8 shown).
[0064] 2) Mott-Schottky curves of ETTAB-DTTzDo-AG samples with different monomer concentrations.
[0065] A working photoelectrode was constructed using ETTAB-DTTzDo powder. 10 mg of ETTAB-DTTzDo powder and 100 μL of Nafion solution were mixed in 900 μL of DMF as the stock solution. 10 μL of the prepared solution was drop-coated on a clean FTO glass and the DMF was dried in a vacuum environment to obtain the ETTAB-DTTzDo-based photoelectrode. The ETTAB-DTTzDo-based electrode was used as the working electrode, with a size of 1.0 × 1.0 cm 2 The platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and a three-electrode system was used to perform the Mott-Schottky plot (e.g. Figure 10 The flat bands of ETTAB-DTTzDo-AG samples with different monomer concentrations are calculated to be -0.49V, -0.51V and -0.54V respectively, and the corresponding photocurrent diagrams (as shown in FIG Figure 9It can be seen that all the ETTAB-DTTzDo-AG samples with different monomer concentrations have photoelectric phenomenon. According to the valence band position of electrochemical test and the obtained band gap width, the band structure diagram of the ETTAB-DTTzDo-AG sample with different monomer concentrations can be obtained (as shown in Figure 11 FIG. 2).
[0066] Photocatalytic hydrogen peroxide production experiment
[0067] 10 mg of the gel sample was weighed into a 50 mL Schlenk tube, and 20 mL of deionized water was added. The atmosphere was replaced with oxygen by multiple vacuum-purging oxygen circulation cycles, and the LED lamp was used as the light source for illumination for two hours. After the reaction was completed, the content of hydrogen peroxide in the reaction solution was determined by colorimetric titration. After 5 mL of the reaction solution was filtered to obtain a clear solution, it was poured into a 25 mL volumetric flask, 2 mL of chromogenic agent was added, and then the volume was adjusted. The absorbance at 410 nm was tested by ultraviolet spectrophotometry with water as the reference liquid. According to the standard curve, the content of hydrogen peroxide was calculated, and then the H2O2 production rate was obtained (as shown in Figure 12 FIG. 3). Figure 12 It can be seen that the photocatalytic rate thereof in pure water can reach 4435 μmol g -1 h -1 , and the photocatalytic rate thereof under the condition that the sacrificial reagent is benzyl alcohol can reach 8240 μmol g -1 h -1 .
Claims
1. An N, S fused ring aromatic hydrocarbon molecule, characterized in that: Its structural formula is shown in Formula I:
2. The method for preparing a N, S fused ring aromatic hydrocarbon molecule according to claim 1, characterized in that: The preparation method comprises: using a hydrothermal reaction to prepare the N,S fused-ring aromatic hydrocarbon molecule from an organic monomer and a reaction solvent; wherein the organic monomer is 2,2'-((1,2,4,5-tetrazine-3,6-diyl)bis(sulfonamide))diacetic acid, and the reaction solvent is at least one of N,N-dimethylacetamide, methanol, or N,N-dimethylformamide; Furthermore, the hydrothermal reaction conditions are: heating the organic monomer and the reaction solvent at 60-120° C. for 3-5 days.
3. Use of the N, S fused ring aromatic hydrocarbon molecule according to claim 1 in the preparation of porous organic polymer gels, organic photoelectric materials or catalytic materials.
4. A porous organic polymer gel, characterized in that The polymer gel is prepared by reacting an aldehyde-containing organic monomer with the N,S fused ring molecule according to claim 1; wherein the aldehyde-containing organic monomer contains at least four aldehyde groups; Furthermore, the aldehyde-containing organic monomer is selected from at least one of the following substances: 4,4',4",4"'-(ethylene-1,1,2,2-tetrayl)tetrabenzaldehyde, 1,3,6,8-tetrakis(4-formylphenyl)pyrene, s-hexa(4-formylphenyl)benzene or 1,2,4,5-tetrakis(4-formylphenyl)benzene; Furthermore, the molar ratio of the aldehyde-containing organic monomer to the N,S fused ring molecule is 0.04-0.10: 0.08-0.
20.
5. The method for preparing the porous organic polymer gel according to claim 4, characterized in that: The preparation method comprises: reacting an aldehyde-containing organic monomer and the N,S fused ring molecule in the presence of a solvent 1 and a catalyst at 110 to 140° C. for 2 to 7 days to obtain the porous organic polymer wet gel; wherein the solvent 1 is N,N-dimethylacetamide or N,N-dimethylformamide; and the catalyst is selected from the group consisting of pure acetic acid, triethylamine, phosphoric acid, and triisopropylamine. Furthermore, the molar volume ratio of the aldehyde-containing organic monomer to the solvent 1 is: 0.05-0.10 mmol: 1 mL; Furthermore, in the above-mentioned method for preparing the porous organic polymer gel, the volume ratio of the catalyst to the solvent 1 is 0.05-0.20:0.5-1.
6. The method for preparing the porous organic polymer gel according to claim 5, characterized in that: The porous organic polymer gel is prepared by ultrasonically treating an aldehyde-containing organic monomer, an N,S fused ring molecule, and a solvent 1 to fully dissolve the aldehyde-containing organic monomer, then adding a catalyst and freezing the reaction device in liquid nitrogen. After at least three cycles of freezing-vacuuming-thawing, the air in the reaction device is exhausted. The reaction device is then sealed with a flame gun at 600-1200° C., dried at 110-140° C. for 2-7 days, and then cooled to room temperature to obtain the porous organic polymer gel wet gel. Further, the obtained porous organic polymer gel wet gel is processed into a dry gel.
7. Use of the porous organic polymer gel according to claim 4 in photocatalysis, gas separation, ion conduction, ion separation or molecular separation.
8. A photocatalytic material, characterized in that: The photocatalyst material is an aerogel material prepared by reacting an aldehyde-containing organic monomer with the N, S fused ring molecule according to claim 1.
9. A photocatalytic material according to claim 8, characterized in that: The photocatalytic material produces H2O2 at a rate of 4435 μmol g in pure water without sacrificial reagents. -1 h -1 ; Furthermore, the photocatalytic material produces H2O2 at a rate of 8240 μmol g -1 h -1 .
10. The method for preparing a photocatalytic material according to claim 8 or 9, characterized in that: The preparation method comprises the following steps: firstly reacting an aldehyde-containing organic monomer and an N,S fused ring molecule under the action of a solvent 1 and a catalyst at 110 to 140° C. for 2 to 7 days to obtain the porous organic polymer wet gel; then processing the wet gel into a dry gel to obtain the photocatalytic material; wherein the solvent 1 is N,N-dimethylacetamide or N,N-dimethylformamide; and the catalyst is selected from the group consisting of pure acetic acid, triethylamine, phosphoric acid, or triisopropylamine.
Citation Information
Cited By
Porous organic polymer hybrid gel with long exciton lifetime and preparation and application thereof
CN122277842A